Effect of Different Potential Combinations on Characteristics of Nanoparticles formed by Dewetting. - Stoker, T. McKay; Roberts, Nick A. (Journal of the Utah Academy of Sciences, Arts & Letters, 2017)
Dewetting (the contraction of a thin film into droplets on a substrate) may be used to self-assemble nanoparticles. Understanding how to direct the assembly of nanoparticles from dewetting is critical to effective application of the method. In previous work, it was found that adding a capping layer over the film alters the final morphology of nanoparticles. Choosing cap and substrate substances that have certain potentials with the film is a possible technique to control dewetting. We studied the effect of changing these potentials in various combinations with the aid of molecular dynamics (MD) simulations. The size and characteristics of the nanoparticles formed were analyzed. We found that the higher energy surface, whether the substrate or cap, dominates dewetting. We also found that the higher energy potentials caused smaller nanoparticles to form or even to keep the film wet to the surface.